2009
DOI: 10.1155/2009/379578
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Endometriosis Mimicking Colon Cancer on a Virtual Colonoscopy Study: A Potential Pitfall in Diagnosis

Abstract: Colonic endometriosis has been reported in the literature to mimic colon cancer. Patients can present with symptoms almost identical to colon cancer. We present an exemplary case of a woman who was found to have a mass on conventional colonoscopy. Virtual colonoscopy was instrumental in characterizing the obstructive sigmoid mass. A biopsy of the mass revealed sigmoid endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Little is known on the extragonadal development of endometrial tissue foci, and both the vascular dissemination and implantation theory might seemingly explain such ectopic implants (3). The frequency of extragonadal endometriosis in the bowel is estimated to involve 3%-37% of women with pelvic endometriosis, and most lesions are found in the sigmoid colon and rectum (4).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known on the extragonadal development of endometrial tissue foci, and both the vascular dissemination and implantation theory might seemingly explain such ectopic implants (3). The frequency of extragonadal endometriosis in the bowel is estimated to involve 3%-37% of women with pelvic endometriosis, and most lesions are found in the sigmoid colon and rectum (4).…”
Section: Discussionmentioning
confidence: 99%
“…Either through its symptoms and signs or its clinical picture, endometriosis can imitate other diseases with similar signs and symptoms. Samet et al [15] discuss colonic endometriosis, which perfectly imitates colon cancer: the lesion was not found to differ from the cancer under virtual endoscopy. Another example of imitation can be seen in another case opposite to the one described here.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with 'deep infiltrating endometriosis of the rectum' (DIER), symptoms can be very puzzling, usually similar to irritable bowel syndrome and may sometimes even mimic colonic adenocarcinoma. Symptoms include diarrhea, constipation, tenesmus, dyschezia, rectal bleeding, change of bowel habits, and in severe cases acute intestinal obstruction or even perforation [22][23][24]. Pisanu et al [25] in 2010 reported the first case of spontaneous rectal perforation from endometriosis during pregnancy outlining that this condition could have serious and unexpected presentations even after surgical control.…”
Section: Introductionmentioning
confidence: 99%